IMPLEMENTASI PENDIDIKAN RAMAH ANAK MADRASAH DI MI TARBIYATUL ULUM BATU MALANG - Wahida Sukma; Mohammad Afifulloh; Muhammad Sulistiono (JPMI: Jurnal Pendidikan Madrasah Ibtidaiyah, 2019)
AbstractEducation is all conscious activities or efforts carried out by edducators to students on all aspect of personality development both physically and spiritually. Every student has their right,both the raight to obtain education and the raight to protect themselves, various forms of violence because every student has the right to obtain knowledge withaout any discrimination/violence. The phenomenon of violence against children has made MI Tarbiyatul Ulum Batu make efforts in overcoming it through the Child Friendly Education Program and always to implement child friendly education program and always to implement child friendly educations in the school environment. Based on the results of observations made at MI Tarbiyatul Ulum Batu, that the school is implementing Child Friendly Educations, this is seen from the way all educations sttaf in the school environment treat their students without any acts of physical violence. To achieve these objectives above research with a type of qualitative research. The procedure of data collection is done using observation methods. The implementation of child friendly education at MI Tarbiyatul Ulum Batu has been quite good even though there is still something that must be improved for its impermeability.Keywords : Implementation, Education, Child Friendly